Early invasive or conservative strategies for older patients with acute coronary syndromes: A Meta-Analysis - Reddy, Rohin K.; Koeckerling, David; Eichhorn, Christian; Jamil, Yasser; Ardissino, Maddalena; Braun, Volker; Abu Sharar, Haitham; Frey, Norbert; Howard, James P.; Ahmad, Yousif (JAMA internal medicine, 2025)
The optimal management strategy for older patients who present with acute coronary syndrome (ACS) remains unclear due to a paucity of randomized evidence. New large and longer-term randomized data are available.To test the association of an early invasive strategy vs a conservative strategy with clinical outcomes for patients 70 years or older who present with ACS.A literature search strategy was designed in collaboration with a medical librarian. MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials were systematically searched ,with no language restrictions from inception through October 2024. Bibliographies of previous reviews and conference abstracts from major cardiovascular scientific meetings were handsearched.Studies were deemed eligible following review by 2 independent, masked investigators if they randomly allocated patients 70 years or older who presented with ACS to early invasive or conservative management and reported clinical end points. Observational analyses were excluded. No trials were excluded based on sample size or follow-up duration.Data were extracted independently and in triplicate. Clinical end points were pooled in meta-analyses that applied fixed-effects and random-effects modeling to calculate summary estimates for relative risks (RRs) and hazard ratios, along with their corresponding 95% CIs.The prespecified primary end point was all-cause death. Secondary end points included recurrent myocardial infarction (MI), repeated coronary revascularization, major bleeding, cardiovascular death, death or MI, stroke, heart failure hospitalization, major adverse cardiac events, major adverse cardiovascular or cerebrovascular events, and length of hospital stay.The sample size-weighted mean age of participants across included trials was 82.6 years, and 46% were female. In the pooled analysis, there was no significant difference in all-cause death between the invasive and conservative strategies (RR, 1.05; 95% CI, 0.98-1.11; P = .15; I2 = 0%). An early invasive strategy was associated with a reduced risk of recurrent MI of 22% (RR, 0.78; 95% CI, 0.67-0.91; P = .001; I2 = 0%) and repeated coronary revascularization during follow-up of 57% (RR, 0.43; 95% CI, 0.30-0.60; P < .001; I2 = 33.3%). However, an invasive strategy was associated with an increased risk of major bleeding (RR, 1.60; 95% CI, 1.01-2.53; P = .046; I2 = 16.7). No differences were observed in secondary end points. Results in the non-ST-elevation ACS population were consistent with the overall findings.The results of this systematic review and meta-analysis suggest that, in older patients with ACS, an early invasive strategy was not associated with reduced all-cause death compared with conservative management. An early invasive strategy was associated with reduced recurrent MI and repeated coronary revascularization during follow-up but increased risk of major bleeding. Competing risks associated with an early invasive strategy should be weighed in shared therapeutic decision-making for older patients with ACS.